2003
DOI: 10.1046/j.1537-2995.2003.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of HBV DNA detection in US blood donors testing positive for the presence of anti‐HBc: implications for transfusion transmission and donor screening

Abstract: Anti-HBc screening detects HBsAg EIA-negative, HBV-infected donors at a rate comparable to the estimated residual risk for HBV window-period infections. The low viral load in the HBV DNA-positive samples suggests that minipool NAT will not detect most potentially infectious units from anti-HBc-positive donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
185
5
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(205 citation statements)
references
References 23 publications
(63 reference statements)
11
185
5
4
Order By: Relevance
“…The transmission routes of HBV through blood transfusion [8,9] ; body fluids including serum, saliva, vaginal secretions, breast milk, and semen [10][11][12][13][14] ; intrauterine infection [15,16] ; cell, tissue, and organ transplantation [17,18] and others including hemodialysis units and intravenous drug injection [19][20][21][22][23] have been documented. Hadchouel et al [24] , using molecular hybridization, confirmed the presence of integrated HBV DNA sequences in spermatozoa from two of three patients with HBV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission routes of HBV through blood transfusion [8,9] ; body fluids including serum, saliva, vaginal secretions, breast milk, and semen [10][11][12][13][14] ; intrauterine infection [15,16] ; cell, tissue, and organ transplantation [17,18] and others including hemodialysis units and intravenous drug injection [19][20][21][22][23] have been documented. Hadchouel et al [24] , using molecular hybridization, confirmed the presence of integrated HBV DNA sequences in spermatozoa from two of three patients with HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In China, 500 000 to one million new cases appear every year [1] and 73% of patients with chronic hepatitis and 78% and 71% of those with cirrhosis and HCC, respectively, are HBsAg positive [7] . Therefore, studies on transmission of HBV are of substantial importance in virology as well as in public health.The transmission routes of HBV through blood transfusion [8,9] ; body fluids including serum, saliva, vaginal secretions, breast milk, and semen [10][11][12][13][14] ; intrauterine infection [15,16] ; cell, tissue, and organ transplantation [17,18] and others including hemodialysis units and intravenous drug injection [19][20][21][22][23] have been documented. Hadchouel et al [24] , using molecular hybridization, confirmed the presence of integrated HBV DNA sequences in spermatozoa from two of three patients with HBV infection.…”
mentioning
confidence: 99%
“…Özellikle HBV S geni "a" determinant bölgesin-de oluşan mutasyonlar sonucu, rekombinant aşılar ile immunize edilen çocuklarda antiHBs ile birlikte replikasyonun görüldüğü aşı kaçak mutantlar, karaciğer transplantasyonu yapılan ve reenfeksiyonu önlemek için HBIG verilen hastalarda immün kaçak mutantlar, antijenik yapılarındaki değişiklik nedeniyle HBsAg tanısında kullanılan bazı testler tarafından saptanamayan tanısal kaçak mutantlar bildirilmiştir [7,40,41] [42]. Ayrıca izole antiHBc IgG pozitif örnekler-de tekrarlanan testler sonucunda değişen oranlarda (%35'e varan) yalancı antiHBc IgG pozitiflikleri olduğu bildirilmiştir [7,43]. Bu durumların dışında kan transfüzyonunu takiben veya anneden bebeğe antikorların pasif olarak aktarımı, HBV antijenlerine karşı humoral yanıtta bir bozukluk olması ya da özellikle diyabetliler ile böbrek hastalarında sık görülen antiHBs oluştura-mama durumunda, mutant suşlarla oluşan enfeksiyonlarda, HCV veya diğer viral etkenler ile koenfeksiyon durumunda ve son olarak düşük replikasyon seviyesi ile gerçek bir OHB durumunda izole antiHBc IgG pozitifliği görülebilir [3,4].…”
Section: Patogenez Ve Klinikunclassified
“…Bunlar HBsAg'nin değişken varlığı, bazı bireylerde HBsAg'nin testlerin cut-off değerinin altında kalması, HBsAg tanınmasını engelleyen mutasyonlar, HBV DNA pozitif HBV aşısı olmuş donörlerde görülebilen HBsAg yokluğu, kronik enfeksiyonda HBsAg ve HBV DNA seviyeleri arasında korelasyon eksikliği, antiHBc IgG pozitif kan donörlerinin büyük kıs-mında HBsAg yokluğu olarak sıralanabilir [64]. OHB'nin neden olabileceği olası transfüzyon ile HBV bulaşını antiHBc IgG taranmasının önleyebileceğini belirten pek çok çalış-ma mevcuttur [23,43]. Ancak her ne kadar bulaşı azalttığı gös-terilmiş olsa da antiHBc IgG reaktif örneklerde değişen oranlarda yalancı pozitiflikler sonucu donör kaybı, antiHBc IgG prevalansının %10'dan yüksek olduğu ülkelerde ek donör kaybında artış, pencere dönemi bulaşlarını önlemede yetersizliği ve seronegatif OHB bulaşını da önleyememesi antiHBc IgG'nin tarama testi olarak kullanımında karşımıza çıkan problemler olarak tariflenmektedir [3,7,43,64].…”
Section: Tanı Ve Taramaunclassified
See 1 more Smart Citation